Enhancing Accessibility for Disabled Students through Video-Based Learning and Sign Language - Junaedi, Ahyar; Rafii, Mohamad; Mujizatryo, Andykha; Sintaman, Putri Irianti; Risdayanti, Adhelwis Sekar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study focuses on addressing the accessibility challenges faced by students with disabilities in higher education by integrating sign language videos with PowerPoint presentations. The objective is to improve learning outcomes and inclusivity, particularly for students with hearing impairments. Using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional model, the research developed a video-based learning system tailored to the needs of disabled students. Data were collected from students at faculty of business and informatics, palangkaraya muhammadiyah university. Findings reveal significant improvements in accessibility, engagement, and comprehension, with a 38% increase in material access and a 31% improvement in understanding complex concepts. The study concludes that incorporating sign language into educational content not only facilitates better learning outcomes but also promotes active student participation. This research highlights the potential for future development of assistive technologies to create inclusive learning environments in higher education.